(untitled) (Homoeopathy for All, 2025)
The selection of an appropriate homoeopathic remedy is guided by the identification of striking, singular and peculiar symptoms, as emphasized by Dr. Hahnemann in the Organon of Medicine. Among these, food desires and aversions serve as key indicators in individualizing a case and forming the totality of symptoms. Various repertories, including those by Dr. Kent, Dr. Boenninghausen, Dr. Boger and Dr. Guernsey, categorize these rubrics differently. Dr. Robin Murphy’s Homoeopathic Medical Repertory uniquely compiles food-related rubrics in a dedicated ‘Food’ chapter, offering a structured approach to analyzing desires, aversions, aggravations, and ameliorations related to food and drink. This article explores the significance of the Food chapter in Murphy’s Repertory, comparing its approach to other repertories and highlighting its clinical utility in homoeopathic practice.